123 Early Postural Stability Changes in Patients Undergoing Correction of Spinal Deformity. (April 2023) - Keister, Alex; Grossbach, Andrew James; Toop, Nathaniel; Mallory, Noah; Gibbs, David Charles; Xu, David S.; Viljoen, Stephanus
Abstract : INTRODUCTION: Adult spinal deformity (ASD) is an increasingly prevalent cause of pain and disability. It is known that ASD correction results in improved alignment, but not whether this alignment results in objective improvements in postural stability. METHODS: A retrospective review of a prospectively maintained database identified 16 patients undergoing ASD correction surgery with five or more segments. Balance was assessed via a force plate pre- and three months postoperatively. Participants were instructed to stand still, with their hands at their sides and eyes open. Center of pressure (COP) and center of gravity (COG) parameters were analyzed and used to derive head sway in the Dubousset cone of economy (COE). Spinopelvic parameters (PI, PT, SVA, and LL) on standing scoliosis radiographic films were also measured pre- and three months postoperatively. RESULTS: In our 16-patient series, there was a mean age of 61.3 years-old, and a median of 10 segments fused. Postoperative force plate assessment showed a decrease in total COP sway and sway velocity (p < 0.05). Coronal COP sway and sway velocity also decreased (p < 0.05). There was a decrease in total, coronal and sagittal COG sway and sway velocity postoperatively (p < 0.05). In the COE, total head sway decreased (p < 0.05). PT remained unchanged following surgical correction, while LL and SVA improved from 44.9° to 56.7° (p < 0.01) and 82.2 to 22.5 mm (p < 0.01), respectively. PI-LL mismatch also improved from 16.2° to 4.8° (p < 0.01). CONCLUSIONS: Following long segment fusion for ASD, postural stability may improve as early as three months, concomitant with improved spinopelvic alignment. We believe force plate assessment warrants further study for postoperative evaluation of postural alignment and clinical outcomes in ASD patients.